Entrepreneurial intentions and gender: pathways to start-up. Issue 3 (20th August 2019) - Nikou, Shahrokh; Brännback, Malin; Carsrud, Alan L.; Brush, Candida G.
Abstract : Purpose: The purpose of this paper is to revisit the conceptualization and measurement of entrepreneurial intentions. Significant studies anchored in the Theory of Planned Behavior use causal statistical approaches to entrepreneurial intentions. This methodological approach, leads to the conclusion that there is a single pathway for all groups of people to achieve business start-up. Even though theory suggests approaches by women entrepreneurs to start a business may be influenced by different factors from those influencing men, results are inconclusive in these analyses. The authors argue that methodological preferences for linear, causal analytical approaches limit the understanding of gender similarities and differences in the business start-up process. The authors propose that when considering diverse samples, it is unreasonable to assume there is only a single pathway leading to business start-up. Design/methodology/approach: Building on fuzzy-set Qualitative Comparative Analysis (fsQCA) and data set of 2, 038 respondents, the authors investigate factors predicting the intentions to start a business and evaluate the alternative conjunctive paths that emerge. Findings: The fsQCA results shows that the relationship among conditions leading to entrepreneurial intentions is complex and is best represented as multiple and conjectural causation configurations. In other words, there are multiple significant pathways (refers to equifinality) that predict intentions to start a business start-up, and there are significant differences by gender. Originality/value: This study is one of the first to examine the roll of gender as a sperate condition in the analysis. This paper offers implications for theory and future research and highlights the complexity of this domain.